Round table discussion on abolishing death penalty - UiTM, Faculty of Law (Faculty of Law, 2019)
On Tuesday, 19 March 2019, law lecturers from the Faculty of Law, UiTM were invited to attend the roundtable discussion on abolishing the death penalty. The roundtable discussion was hosted by the International Institute of Advanced Islamic Studies (IAIS) Malaysia. The half day discussion was attended by a wide array of participants of different professional backgrounds. The objectives of the discussion are to provide a platform for scholars, law enforcers and policy makers to discuss at length the feasibility of abolishing the death penalty. Besides that, the round table discussion aims to seek possible solutions from the Islamic perspective and to understand the reasoning behind abolishing or retaining the death penalty. The speakers were Prof. Dr. Mohammad Hashim Kamali, Assoc. Prof. Dr. Shamrahayu A.Aziz, Dato’ Mah Weng Kwai and Assoc. Prof. Dr. Mohamed Azam Mohamed Adil. The speakers voiced their opinions on the right to life based on Shariah and International law perspectives. Besides the speakers, a few participants gave their ideas on the issue of whether to abolish or retain the death penalty in Malaysia. Dr. Nur Ezan Binti Rahmat, Encik Ahmad Shukree Mohd Salleh, Puan Mimi Sintia Binti Hj. Bajuri, Puan Che Audah Hassan, Dr. Normawati Hashim and Dr. Faridah Hj. Hussain represented the Faculty to this roundtable discussion.